Cattle Grazing Does Not Alter Early Season Insect Community Composition in Tallgrass Prairies - Barajas, Aster; Kim, Tania (My University, 2023)
Prairie ecosystems are known to have cattle that graze on the different grasses, plants, and flowers. This is known to negatively impact insect communities because of the defoliation, or the removal of plants, of the environment. As cattle graze and change the environment of prairie foliage, arthropods lose valuable resources that are essential to mating, predation, and development. The current hypothesis is that insect communities in ungrazed land have greater order-level richness and insect abundance than communities in grazed land. In order to find what communities were present, 10 sites throughout eastern Kansas were sampled using sweep net methods. The sites are divided evenly into 5 grazed and 5 ungrazed land, and sweeps are conducted by moving a sweep net in a serpentine pattern through foliage along 2 50 meter transects. The collected insects are counted and identified to the order level under a microscope, then processed using Microsoft Excel’s data analysis tools. The experiment resulted in a higher insect abundance in grazed sites than in ungrazed sites, and slightly higher order richness in not grazed sites than in grazed sites. However, these results are not significant. There were differences found in community composition with Coleoptera (beetles) numbers differing in grazed (10%) and ungrazed sites (16%), Neuroptera (lacewings) not being present in grazed sites, and Odonata (dragon/damselflies) not being present in ungrazed sites. Further investigation into these differences could give deeper insights to the effects of cattle grazing on these communities.
Keywords: Cattle grazing; Insects; Ecology; Eastern Kansas; Tallgrass praries; USDA NIFA 2019-67032-29071